A Facile Synthesis of Bimetallic Copper-Silver Nanocomposite and Their Application in Ascorbic Acid Detection - Murugan, Ridhu Varshini; Sridharan, Gokul; Atchudan, Raji; Arya, Sandeep; Nallaswamy, Deepak; Sundramoorthy, Ashok K. (Current Nanoscience, 2025)
BackgroundAn important antioxidant, ascorbic acid, must be detected in several industrial samples collected from food, pharmaceuticals, and water treatment plants. Herein, we reported a method to produce a bimetallic copper-silver (Cu-Ag) nanocomposite and used it in the development of very sensitive and selective electrochemical sensor for the detection of ascorbic acid.MethodsA simple chemistry concept was used during the synthesis process to reduce the cost while minimizing the use of dangerous chemicals and minimizing the environmental impact. The Strobilanthes kunthiana leaves extract effectively reduced the copper and silver ions, resulting in the creation of an extremely stable and evenly distributed Cu-Ag nanocomposite.ResultsAs-prepared bimetallic Cu-Ag nanocomposite exhibited outstanding electrochemical activity against ascorbic acid oxidation. The nanocomposite was examined using field emission scanning electron microscopy (FE-SEM), energy dispersive spectroscopy (EDS), elemental mapping (EMap) and X-ray diffraction analysis (XRD) to ascertain its composition, structure, and stability. Using cyclic voltammetry (CV), the electrochemical performance of the nanocomposite and also the detection of ascorbic acid were carried out. The bimetallic Cu-Ag nanocomposite also exhibited better long-term stability and fouling resistance, making it appropriate for use in real-world applications and complex sample matrices.ConclusionThe bimetallic Cu-Ag nanocomposite coated electrode was used to detect the concentration of ascorbic acid by amperometry. As a result, this study offered a simple chemical method for creating a bimetallic copper-silver nanocomposite with superior electrochemical qualities for the accurate detection of ascorbic acid.
Keywords: Strobilanthes kunthiana